HUBUNGAN CARING PERAWAT DENGAN TINGKAT KECEMASAN KELUARGA PASIEN DI RUANG INTENSIVE CARE UNIT (ICU) : LITERATUR REVIEW - Nurhilmiah, Tia (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2024)
Nurses who have a caring attitude have an impact on increasing confidence which has an impact on patient and family satisfaction in the condition of patients who are being treated in the ICU room, the family remains in a controlled mood so that caring is effective in reducing family anxiety. The purpose of this literature study can explain the relationship between nurses' caring behavior and the level of anxiety of patients and families in the ICU room. The method used was in the form of a literature study or literature review with a procedure for searching and selecting articles based on meta analysis (PRISMA) so that 16 selected articles were obtained that were worthy of analysis. The databases used in this study are Google Scholar, Pubmed and SCIENCE DIRECT with a publication span of the last 5 years, namely from 2019 to 2024 with fulltext article types. The results of the review of the 16 articles reviewed stated that the results of the statistical analysis test found that there was a correlation between the respondent's perception of nurse caring and the level of anxiety felt by the patient's family with a p-value of 0.05. The conclusion of this literature review is that there is a relationship between nurse caring and the level of anxiety of patients' families in the ICU room